2014
DOI: 10.1617/s11527-014-0382-8
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical modeling of composite-to-brick bond

Abstract: In masonry components strengthened with externally bonded composites, good bonding is one of the most important aspects governing structural behavior, since failure usually takes place with detachment between reinforcement and substrate. This type of event is a brittle, sudden and therefore undesirable failure mechanism; nor does it allow the full strength of the reinforcement to be exploited. Many experimental data on bonding have recently become available from a Round Robin Test carried out within the framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Detailed knowledge of the interface behaviour allows to perform an accurate numerical analysis, where between the FRP reinforcement and the masonry substrate can be placed a cluster of zeroethickness interface elements [40,41] characterized by the analytical laws calibrated as described.…”
Section: Local Interface Lawsmentioning
confidence: 99%
“…Detailed knowledge of the interface behaviour allows to perform an accurate numerical analysis, where between the FRP reinforcement and the masonry substrate can be placed a cluster of zeroethickness interface elements [40,41] characterized by the analytical laws calibrated as described.…”
Section: Local Interface Lawsmentioning
confidence: 99%
“…Numerous experimental studies of FRP–substrate interfaces have shown that the FRP stiffness and the substrate strength are the main parameters affecting the bond–slip relationship [ 20 , 29 , 34 , 38 , 41 , 54 ]. In this section, firstly, the effects of single variables of FRP stiffness and brick strength on the bond–slip relationship at the FRP-to-brick interface were investigated.…”
Section: Parameter Study On Dynamic Behaviormentioning
confidence: 99%
“…The model proposed in this paper is expected to be useful in all those mechanical problems where solid interfaces together with geometrical and material nonlinearities have to be taken into account in a simple and reliable way at the macroscale. Potential applications could range from the bonding characterisation of cold-welded metallic joints (Zhang and Bay, 1997;Lu et al, 2010) to the collapse of FRP adhesive joints (Ascione, 2009b,a) and the simulation of masonry-FRP bond (Basilio et al, 2014;Ceroni et al, 2014), with special attention to the modelling of GFRP beams obtained by bonding simple panels (Ascione et al, 2015). In particular, its applicability in modelling brick/mortar interfaces is illustrated in Section 4.…”
Section: Introductionmentioning
confidence: 99%